Diversité des macroinvertébrés benthiques des rivières du nord-est de l’île d’Idjwi, République Démocratique du Congo - Michael Baraka Nyakabeji; Éric Mihingano Mushagalusa; Jean-Jacques Mashimango Bagalwa; Augustin Kanyunyi Basabose (VertigO, 2023)
The purpose of this study was to determine the diversity of benthic macroinvertebrates and the quality of rivers in the North East of Idjwi Island, Democratic Republic of the Congo. Macroinvertebrates were collected from June to September 2017 in 4 rivers: Nyamisheke, Tama, Miriri and Nyahonga. Eight sampling trips were conducted and 32 samples taken in 20 sites (5 sites per river) using a dip net. The results obtained revealed 5531 specimens captured in total. These macroinvertebrates are distributed in 3 phyla (arthropods, mollusks and annelids), 5 classes (insects, crustacea, gastropods, oligochaetes and achaetes), 11 orders and 43 families. Their relative abundance varies according to the rivers: Nyamisheke (31%), Tama (28%), Miriri (25%) and Nyahonga (16%). The Shannon index calculated variates between 1.4 and 2.6 and reflects a disproportionate diversity across sites. Overall, the stations located upstream are more diverse than those located downstream. However, the Global Normalized Biological Index (GNBI) values indicate significant pollution in the four rivers, which is a consequence of the multiple anthropogenic activities (overexploitation of sand, fishing, washing up, bathing and presence of agricultural organic waste) in and around these rivers. This excessive pollution negatively impacts the diversity and abundance of macroinvertebrates in these sites. Therefore, measures should be taken by the competent structures to discourage these anthropic activities in order to preserve the health of these river ecosystems and of human populations.